Geology and Coal Deposits of Hasler Creek Area, British Columbia: - Spivak, J. (Author); Geological Survey of Canada (Author) (Dept. of Mines and Resources, 1944)
by J. Spivak. Paper (Geological Survey of Canada) 44-7.